The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3889/oamjms.2022.7829
|View full text |Cite
|
Sign up to set email alerts
|

Ligasure™ Hemorrhoidectomy versus Conventional Hemorrhoidectomy: Comparison in Outcome

Abstract: BACKGROUND: Hemorrhoids are a common problem faced in the surgical practice that cause a variety of symptoms ranging from bleeding per rectum to prolapsed, non-reducible and painful anal masses. Therefore, hemorrhoidectomy is one of most frequently performed surgical procedures worldwide. AIM: In this study, we will compare between the conventional surgical method and between LigaSure™ hemorrhoidectomy. PATIENTS AND METHODS: All 120 patients underwent hemorrhoidectomy by conventional and LigaSure™ method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…16 This study found insignificant difference in urinary retention and the results matches with previously reported studies where similar insignificant difference was reported by Sakr et al, Alhamdany et al and Abdelaziz and Halim. 15,17,18 Frequency of anal stenosis between the groups in this study also did not differ significantly and the findings are similar to that of Haksal et al and Sakr et al 16,15 In the light of findings of this study, Ligasure Haemorrhoidectomy can be promoted for management patients with third and fourth degree haemorrhoids in future. A very key limitation to this trial was that the other outcome measures of surgery e.g.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…16 This study found insignificant difference in urinary retention and the results matches with previously reported studies where similar insignificant difference was reported by Sakr et al, Alhamdany et al and Abdelaziz and Halim. 15,17,18 Frequency of anal stenosis between the groups in this study also did not differ significantly and the findings are similar to that of Haksal et al and Sakr et al 16,15 In the light of findings of this study, Ligasure Haemorrhoidectomy can be promoted for management patients with third and fourth degree haemorrhoids in future. A very key limitation to this trial was that the other outcome measures of surgery e.g.…”
Section: Resultssupporting
confidence: 89%
“…The experiment and the control group did not possess any significant inherit difference as shown by chi-square and independent sample t tests. 17,15,18 We found male predominance in the study population with a male to female ratio of 1.58:1. Similar male predominance in such patients has been previously reported by some other authors as 1.53: 17,10 We noticed mean bleeding was significantly less in LS group than MM group.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations